Reversal of the Burden of Proof in Money Laundering: A Legal Economic and Business Ethics Perspective - Agustinus Purnomo Hadi; Arizon Mega Jaya; Aristama Mega Jaya (Al-Amwal : Journal of Islamic Economic Law, 2026)
Background: Money laundering originating from corruption has become a serious issue that not only affects law enforcement but also undermines economic stability and business integrity. The practice distorts market mechanisms, creates unfair competition, and contradicts ethical principles in both conventional and Islamic economic systems. Objective: This study aims to analyze the application of the reversal of the burden of proof in money laundering crimes derived from corruption, as well as to examine its role from the perspective of legal economics and business ethics, including Islamic business ethics. Method: This research employs a normative juridical method with statutory and conceptual approaches. Legal materials are collected through literature studies, including legislation, academic journals, and relevant legal doctrines, and are analyzed using qualitative legal interpretation. Results: The findings indicate that the reversal of the burden of proof is an effective legal mechanism in uncovering illicit assets and supporting law enforcement in money laundering cases. From a legal economic perspective, this mechanism contributes to reducing information asymmetry, enhancing transparency, and preventing market distortions. From a business ethics perspective, it promotes accountability and discourages unethical financial behavior. Furthermore, in the framework of Islamic business ethics, money laundering is inconsistent with principles such as honesty (ṣidq), trustworthiness (amānah), and justice (‘adl), thereby justifying stronger legal enforcement. Contribution: This study contributes by integrating criminal law analysis with legal economic and ethical perspectives, particularly Islamic business ethics, thus offering a more comprehensive approach to combating money laundering and strengthening ethical economic systems.